AUGUSTUS BY SUETONIUS: THE MAN AND THE MAKING OF THE GOD - Brandão, José Luís; Leão, Delfim (PHOÎNIX, 2020)
The study focuses on the Life of Augustus by Suetonius, the most complete literary source on the emperor and also the longest Suetonian biography. It analyses the way the author organizes the narrative, selects events and addresses his main topics in order to paint a strongly ideological portrait of Augustus.